The relationship between critical thinking and problem-solving skills in social studies among primary school students - Uus Kuswendi; Bunyamin Maftuh (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Critical thinking skills contribute to the development of problem-solving skills. Therefore, when students use problem-solving skills, they are also using their critical thinking skills. This study aims to analyze the relationship between critical thinking skills and problem-solving skills of primary students. The study used a quantitative, correlational approach and involved 81 students from four primary schools in Cilacap. The research instrument consisted of a critical thinking test based on Facione's indicators, covering interpretation, analysis, evaluation, inference, and explanation, and a problem-solving questionnaire based on Polya's four steps. The four steps consist of understanding the problem, planning a solution, implementing a strategy, and evaluating the results. Data were analyzed using Spearman's rank correlation because neither variable was normally distributed. The results reveal that critical thinking skills and problem-solving skills were in the good category. The Spearman correlation test yielded a coefficient of 0.914 and a significance level of 0.000, indicating a very strong, unidirectional relationship between the two variables. This finding confirms that improving critical thinking skills aligns with improving problem-solving skills, especially in the context of Social Studies, which demands analysis of social issues, logical reasoning, and evidence-based decision-making. The research results are expected to serve as a basis for teachers and schools in designing learning that is more reflective, contextual, and oriented towards strengthening students' critical thinking skills.